2022
DOI: 10.1007/s40120-022-00325-z
|View full text |Cite
|
Sign up to set email alerts
|

MIND Diet Adherence Might be Associated with a Reduced Odds of Multiple Sclerosis: Results from a Case–Control Study

Abstract: Introduction:The Mediterranean Dietary Approaches to the Stop Hypertension (DASH) Intervention for Neurodegenerative Delay (MIND) diet has been shown to have beneficial neuroprotective effects. The purpose of this research was to evaluate the link between the MIND diet adherence and multiple sclerosis (MS), a degenerative neurological illness. Methods: In a hospital-based case-control setting, 77 patients with relapsing-remitting multiple sclerosis (RRMS) and 148 healthy individuals were recruited. A validated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 63 publications
2
11
0
Order By: Relevance
“…Consistent with previous observations, the consumption of other healthy components of the aMED were also associated with a reduced risk of MS in our study, such as legumes, 11,54 fruit, 7,11 and vegetables, 7,54 but only legumes reached signi cance. Surprisingly, MS participants from the International Multiple Sclerosis Microbiome Study (iMSMS) consumed more fruits and vegetables, and scored better overall on a healthy eating index, when compared with household controls (the majority of whom were spouses).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with previous observations, the consumption of other healthy components of the aMED were also associated with a reduced risk of MS in our study, such as legumes, 11,54 fruit, 7,11 and vegetables, 7,54 but only legumes reached signi cance. Surprisingly, MS participants from the International Multiple Sclerosis Microbiome Study (iMSMS) consumed more fruits and vegetables, and scored better overall on a healthy eating index, when compared with household controls (the majority of whom were spouses).…”
Section: Discussionsupporting
confidence: 93%
“…9,53 Similarly, an Iran-based study also observed a lower dietary ber intake among 77 MS cases compared to 148 controls. 54 While no other study assessed whole-grain intake (as a component of food) in MS cases, consumption of whole-grain foods-a healthy component of the aMED-was, although the direction of their ndings was similar to ours, none reached signi cance, at least when adults were asked to recall their prior diet from ages 6 to 20 years. 11 We were able to show a signi cant relationship with a high intake of whole-grain foods associated with a 60% lower odds of MS (OR adj 0.40, 95%CI 0.16-0.97).…”
Section: Discussionsupporting
confidence: 47%
“…Numerous studies have identified foods and food groups that worsen various clinical outcomes of MS. Higher consumption of beef, butter, pastries, and sweets associated with increased risk [130,131] , whereas not consuming meat correlated with reduced disability progression in pwMS [139] . Diets enriched in added sugars and processed foods corresponded with higher burden of metabolic risk factors including abdominal obesity and reduced circulating high-density lipoprotein concentrations among pwMS [140] .…”
Section: Human Ms Dietary Studiesmentioning
confidence: 99%
“…In addition, a large intake of cheese, pastries, sweets, and fast food increases the likelihood of developing MS. As a nutritional component, poultry was also related to increased probabilities. Therefore, it appears that adhering to the MIND diet may be an effective strategy for MS prevention [ 47 ]. However, additional randomized clinical trials are required to advocate the MIND diet as a preventative measure for MS.…”
Section: Reviewmentioning
confidence: 99%